Physical Education, teacher training and inclusion (Research, Society and Development, 2020)
This reflection article deals with Physical Education and its importance for the inclusion of people with disabilities in school. It aims to understand Physical Education together with inclusive education and the process of teacher training in the context of inclusion. Better preparation of Physical Education teachers for inclusive education is needed. Physical Education in the school environment has a strong potential for the inclusion of students regardless of the level and type of disability. Physical Education has a clear function when using games, dance, sports, fights, gymnastics, in promoting the learning of motor gestures, through motor experience and experience in any content worked on. Thus, it is essential that the formation of the Physical Education teacher leads him to a reflexive action and stimulates him to the social context in which the school is inserted, constantly awakening them about his practice and, consequently, the contributions in the student's training.